All Quiet on the Wage Front? Gender, Public-Private Sector Issues, and Rigidities in the Polish Wage Structure - Patrick A. Puhani (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1997)
We analyse the Polish wage and unemployment structure between 1992 and 1995 on the basis of the Polish Labour Force Survey. It is shown that within this period wage inequality has stabilised. Surprisingly, wage inequality is lower in the private than in the public sector. Our test results show that, contrary to the public sector, there are no gender differences in the valuation of human capital in the private sector. This supports the hypothesis that the transition towards a market economy promotes the equality of the sexes. Although the higher?education wage premium has risen significantly over the observation period, the ceteris paribus wage differential between white?collar and blue?collar workers is about zero. Indeed, we find that blue?collar workers as well as workers in the mining, manufacturing, and construction industries have kept or improved their relative wage position despite an increase in unemployment for these groups. There is therefore significant evidence for rigidities in the Polish labour market.
Keywords: J31; J60; 330; wage inequality; wage structure; labour market rigidities; Poland; Lohnstruktur; Lohndifferenzierung; Arbeitsmarktsegmentierung; Geschlecht; Privatwirtschaft; Öffentlicher Sektor; Polen